Social media and local tourist intentions: community-based tourism in Kota Belud, Sabah - Jainol, Nur Fikri; Fatt, Boyd Sun; Mogindol, Spencer Hedley (Universiti Teknologi MARA, Kedah, 2025)
Community-based tourism (CBT) is one of the key drivers of sustainable rural development, offering both economic and cultural benefits to local communities. This research explores the factors that influence local tourists’ intentions to visit CBT destinations by applying the Theory of Planned Behaviour (TPB), which consists of three major aspects, including attitude, subjective norms, and perceived behavioural control. Additionally, this study integrates social media usage as a moderating factor within the rural tourism context of Kota Belud, Sabah. A quantitative approach was employed, using a structured survey adapted from validated TPB frameworks. The survey collected responses using a 5-point Likert scale, focusing on TPB aspects and social media usage. Data were obtained from 261 respondents via convenience sampling, with a response rate of 74.57%. Reliability was confirmed through a pilot test, with Cronbach’s alpha values exceeding 0.70. Partial Least Squares Structural Equation Modelling (PLS-SEM) was applied to analyse TPB relationships and moderating effects. Perceived behavioural control emerged as the strongest predictor of behavioural intention, indicating the importance of logistical convenience. Subjective norms were statistically significant, highlighting how decision-making is influenced by a collectivist societal culture. Attitude showed a weaker yet positive impact. The moderating role of social media usage was statistically insignificant, suggesting that offline influence continues to dominate in rural CBT settings